Comparing the incidence of ventricular arrhythmias during epicardial ablation in swine versus canine models - Caluori, Guido; Wojtaszczyk, Adam; Yasin, Omar; Pesl, Martin; Wolf, Jiří; Belaskova, Silvie; Crha, Michal; Sugrue, Alan; Vaidya, Vaibhav R; Naksuk, Niyada; DeSimone, Christopher V; Killu, Ammar M; et al. (Pacing and clinical electrophysiology, 2019)
BACKGROUND: Choosing the appropriate animal model for development of novel technologies requires an understanding of anatomy and physiology of these different models. There are little data about the characteristics of different animal models for the study of technologies used for epicardial ablation. We aimed to compare the incidence of ventricular arrhythmias during epicardial radiofrequency ablation between swine and canine models using novel epicardial ablation catheters. METHODS: We conducted a retrospective study using data obtained from epicardial ablation experiments performed on swine (Sus Scrofa) and canine (Canis familiaris) models. We compared the incidence of ventricular arrhythmias during ablation between swine and canine using multivariate regression analysis. Six swine and six canine animals underwent successful epicardial radiofrequency ablation. A total of 103 ablation applications were recorded. RESULTS: Ventricular arrhythmias requiring cardioversion occurred in 13.11% of radiofrequency ablation applications in swine and 9.75% in canine (relative risk: 117.6%, 95% confidence interval [CI]: 83.97-164.69, animal-based odds ratio [OR]: .55, 95% CI: .23-61.33; P = .184). When adjusting for application position, duration of ablation and power, the odds of developing potentially lethal ventricular arrhythmia in swine increased significantly compared to canine (OR: 3.60, 95% CI: 1.35-9.55; P = .010). CONCLUSIONS: The swine myocardium is more susceptible to developing ventricular arrhythmias compared to canine model during epicardial ablation. This issue should be carefully considered in future studies.
Keywords: psi; Dogs; animal model electrophysiology; Pericardium; modely nemocí na zvířatech; zvířata; ventricular arrhythmia; katetrizační ablace; Swine; perikard; Retrospective Studies; incidence; Incidence; radiofrequency catheter ablation; komorová tachykardie; retrospektivní studie; Animals; cardiovascular devices; preclinical cardiology; Catheter Ablation; Disease Models, Animal; prasata; Tachycardia, Ventricular